Diagnostic utility and sensitivity of the IGF-1 generation test in children and adolescents with growth disorders: A comparative review with GH stimulation tests: Utility and sensitivity of IGF-1 generation test - Soliman, Ashraf T; Alyafei, Fawzia; Ahmed, Shayma; AlHumaidi , Noora; Hamed, Noor; Elawwa, Ahmed; Alaaraj, Nada; Khalil, Ahmed; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2025)
Background: The IGF-1 (Insulin-like Growth Factor 1) generation test has been widely used in diagnosing growth hormone disorders. However, the diagnostic utility of this test remains debated due to variability in protocols, cut-off points, and sensitivity compared to other methods, particularly the GH stimulation test. Objective: This review seeks to assess the diagnostic value of the IGF-1 generation test (IGF-1 GT) across different growth and puberty-related disorders, the applications across different patient populations, and the diagnostic accuracy in comparison to GH stimulation test. Methods: A comprehensive literature search was conducted across electronic databases (PubMed, Scopus, Web of Science) from 1994 to 2024. Studies were included if they evaluated the IGF-1 GT in diagnosing growth disorders in pediatric populations. IGF-1 cut-off values, test protocols, and diagnostic sensitivity were extracted and compared to those of the GH stimulation test. Results: The IGF-1 GT showed variable sensitivity depending on the diagnosed condition. The IGF-1 GT sensitivity ranged from 30-60%. When compared to the GH stimulation test, which has a sensitivity of 90-100% for diagnosing growth hormone deficiency (GHD), the IGF-1 GT showed a moderate sensitivity (70-90%) and less reliability for idiopathic short stature, Turner Syndrome and Laron Syndrome. Conclusion: The IGF-1 GT is a valuable tool in diagnosing GHD and partial GH insensitivity in specific syndromic disorders, though it illustrates variable sensitivity across different conditions. This variability and differences in testing protocols emphasize the need for further standardization and comparative research with the recombinant GH stimulation test.